AN OPTIMAL PORTFOLIO COMPARISON OF SYARIAH STOCKS BEFORE AND AFTER THE WEAKENING OF THE 2015 INDONESIAN ECONOMY - Ahmad Ridho Darmawan (AFEBI Islamic Finance and Economic Review, 2018)
This paper contains the results of a comparative study of Islamic stock portfolios between the years of 2014-2016. In 2015, Indonesia's economic growth experienced the lowest weakening in the past 6 years. The Jakarta Islamic Index (JII) on 2014 experienced an uptrend, in 2015 it rebounded to a downtrend, and in 2016 an uptrend is experienced again. The purpose of this study was to compare the performance of Islamic stock portfolios before, during and after the weakening of the Indonesian economy and to find the impact of the optimal portfolio strategies in conditions of fluctuating economic growth performance. The population are all the Islamic stocks that are listed on JII in every period during the years of 2013 - 2016. The sample used the Purposive Sampling method, the portfolio performance assessment used the Treynor index and analyzed the data using the Paired-sample T-Test. The results of the study are that (H1) was rejected with a significance value of 0.699> 0.05, (H2) was rejected with a significance value of 0.910> 0.05 and (H3) was rejected with a significance value of 0.797 <0.05. In conclusion, all the hypotheses (H1, H2, H3) are rejected and H0 is accepted. Based on these results, the use of the optimal portfolio method in investment is able to minimize the risks, although it doesn’t eliminate the risk.Keywords: Jakarta Islamic Index, Stock Portofolio, Stock Return, Stock Risk